Efficient world-line-based quantum Monte Carlo method without Hubbard–Stratonovich transformation - J. Wang; W. Pan; D. Y. Sun (Scientific Reports, 2022)
Abstract By precisely writing down the matrix element of the local Boltzmann operator ( $${e}^{-τ h}$$ e - τ h , where $$h$$ h is the Hermitian conjugate pairs of off-diagonal operators), we have proposed a new path integral formulation for quantum field theory and developed a corresponding Monte Carlo algorithm. With the current formula, the Hubbard–Stratonovich transformation is not necessary, accordingly the determinant calculation is not needed, which can improve the computational efficiency. The results show that, the simulation time has the square-law scaling with system sizes, which is comparable with the usual first-principles calculations. The current formula also improves the accuracy of the Suzuki–Trotter decomposition. As an example, we have studied the one-dimensional half-filled Hubbard model at finite temperature. The obtained results are in excellent agreement with the known solutions. The new formula and Monte Carlo algorithm could be applied to various studies in future.